ZSM-48 molecular sieve with low relative crystallinity and preparation method and application thereof
By shortening the reaction time during the hydrothermal synthesis stage of ZSM-48 molecular sieve, a low relative crystallinity ZSM-48 molecular sieve was prepared, and then loaded with precious metal platinum to be used for the hydroisomerization reaction of long-chain normalkanes, the problem of the multiple acidic sites of ZSM-48 molecular sieve in the prior art leads to further isomerization or cleavage of isomerized products, and the isomer selectivity and proportion of single-branched products are improved.
Patent Information
- Application Number
- CN202510016205.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
The ZSM-48 molecular sieve synthesized in the prior art tends to form larger aggregates, resulting in smaller inter-crystalline accumulation pores, which is not conducive to the diffusion of reactants and products. The molecular sieve has more acidic sites, resulting in further isomerization or cleavage of isomerized products, reducing the isomerous selectivity of the reaction.
By shortening the reaction time during the hydrothermal synthesis stage of ZSM-48 molecular sieve, forcibly stopping crystal growth using water-cooling method, ZSM-48 molecular sieve with low relative crystallinity was prepared, and then loaded with precious metal platinum to use for the hydroisomerization of long-chain normal alkanes.
Shortening the hydrothermal synthesis time reduces the relative crystallinity of the molecular sieve, reduces the number and distribution of acidic sites, improves the isomerial selectivity of the catalyst and the proportion of single-branched products, and inhibits the generation of cleavage products.
Smart Images

Figure CN119797391A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical catalysis, and particularly relates to a ZSM-48 molecular sieve with low relative crystallinity, a preparation method and application thereof. Background Art
[0002] Normal-alkanes hydroisomerization catalysts are typically bifunctional catalysts, with a molecular sieve serving as a support and providing acidic sites, while a noble metal is loaded to perform the hydrodehydrogenation. ZSM-48 molecular sieve has a *MRE structure, featuring one-dimensional parallel straight pores with a pore size of 0.53 nm x 0.56 nm. These pore characteristics are well-suited for the hydroisomerization of long-chain normal alkanes, resulting in high selectivity for isomerized products. Furthermore, the molecular sieve possesses relatively moderate acidity, which helps reduce the selectivity of cracking products.
[0003] However, ZSM-48 molecular sieve crystals synthesized using existing methods tend to form larger aggregates, resulting in smaller intercrystalline pores and hindering the diffusion of reactants and products. In the hydroisomerization reaction of long-chain normal alkanes, the molecular sieve's high acidic sites increase the likelihood that the isomerized products will re-contact the acidic sites, causing further isomerization and even cracking, resulting in lower isomerized product selectivity.
[0004] Patent CN 116332201 A prepares a highly dispersible and low-acid ZSM-48 molecular sieve by homogenizing and mixing raw materials, then adding phenolic molecules, followed by crystallization, calcination, and ion exchange. A catalyst supported by this molecular sieve can improve the yield of isomerized products in the hydroisomerization of long-chain normal alkanes, but the in-situ addition of phenolic molecules significantly prolongs the crystallization time of the molecular sieve.
[0005] Therefore, people hope to prepare ZSM-48 zeolites with lower acidity through a simple method, and further load them with precious metal platinum for use in the hydrogenation isomerization reaction of long-chain normal alkanes, reducing the possibility of the products further contacting acidic sites, inhibiting further isomerization and cracking of the isomerized products at the acidic sites of the zeolite, and improving the isomerization selectivity of the reaction.
[0006] In order to solve the above problems, the present invention is proposed. Summary of the Invention
[0007] The present invention aims to provide a method for preparing a ZSM-48 molecular sieve with low relative crystallinity by shortening the hydrothermal synthesis time, and to load the ZSM-48 molecular sieve with low relative crystallinity with precious metal platinum for use in the hydrogenation isomerization reaction of long-chain normal alkanes.
[0008] The method employed in the present invention involves synthesizing ZSM-48 molecular sieves, which include components such as a silicon source, an aluminum source, an alkali, a template, and water. After thoroughly mixing these components, the mixture is transferred to a hydrothermal synthesis reactor for a hydrothermal reaction. Following completion of the reaction, washing, drying, demolding, and ion exchange are performed to produce the hydrogenated molecular sieve. After loading the hydrogenated molecular sieve with precious metal platinum, it undergoes calcination and reduction, and can then be used for the hydroisomerization reaction of long-chain normal alkanes.
[0009] In one aspect, the present invention provides a ZSM-48 molecular sieve with low relative crystallinity. The ZSM-48 molecular sieve has aggregates of 1 to 3 μm, each composed of crystal clusters growing in multiple directions. The crystals in the clusters are columnar, with a diameter of 10 to 40 nm and a length of 100 to 400 nm. More preferably, the width of a single crystal is approximately 25 nm.
[0010] The second aspect of the present invention provides a method for preparing the ZSM-48 molecular sieve with low relative crystallinity according to the first aspect of the present invention, comprising the following steps:
[0011] (1) adding water, alkali solution, template solution, silicon source, and aluminum source to a crystallization kettle in sequence, stirring and mixing them evenly, and then subjecting the mixture to a crystallization reaction. After the hydrothermal reaction proceeds for a certain period of time, the hydrothermal reaction is quenched by water cooling;
[0012] (2) washing the product after the crystallization reaction with water until it is neutral, centrifuging or filtering, and drying to obtain an incompletely crystallized ZSM-48 molecular sieve;
[0013] (3) calcining the incompletely crystallized ZSM-48 molecular sieve in a muffle furnace to remove the template to obtain Na / K-ZSM-48 molecular sieve;
[0014] (4) Converting Na / K-ZSM-48 molecular sieve into H-ZSM-48 molecular sieve to obtain ZSM-48 molecular sieve with low relative crystallinity.
[0015] Preferably, in step (1), the aluminum source is selected from silica-alumina sol, sodium metaaluminate or aluminum sol; the silicon source is selected from silica sol with a SiO2 content of 30% to 40%, silica aerosol, tetraethyl orthosilicate (TEOS) or sodium silicate; the alkali solution is an aqueous solution of NaOH or KOH with a molar concentration of 0.5 to 1.5 mol / L; and the template is selected from hexamethylammonium bromide.
[0016] Silica-alumina sol, such as 056 silica-alumina sol or 007 silica-alumina sol (Nalco); silica sol, such as AS-30, AS-40, etc.
[0017] Preferably, the molar ratio of the aluminum source, water, alkali solution, template solution, and silicon source in step (1) is:
[0018]
[0019]
[0020] The amount of alkali solution is OH - The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, and wherein Q represents a template.
[0021] Preferably, the crystallization reaction temperature in step (1) is 100-260° C., and the crystallization reaction time is 38-48 hours.
[0022] Preferably, the drying temperature in step (2) is 100-200° C., and the drying time is 2-6 hours.
[0023] Preferably, the calcination conditions in step (3) are: first calcining at 500-600°C for 5-8 hours, and then calcining at 600-700°C for 4-6 hours.
[0024] Preferably, the method for converting Na / K-ZSM-48 molecular sieve into H-ZSM-48 molecular sieve in step (4) is to disperse Na / K-ZSM-48 molecular sieve in 0.5-1.5 mol / L ammonium chloride aqueous solution according to a mass ratio of 10, reflux at 70-90°C for 2-6 hours, and dry at 100-150°C to perform ion exchange, and then calcined in a muffle furnace at 500-600°C for 2-6 hours to obtain H-ZSM-48 molecular sieve.
[0025] Preferably, the ion exchange step in step (4) can be performed multiple times to ensure complete ion exchange.
[0026] The third aspect of the present invention provides a ZSM-48 molecular sieve catalyst loaded with precious metal platinum, using the low relative crystallinity ZSM-48 molecular sieve described in the first aspect of the present invention as a carrier, which is loaded with precious metal platinum and used for the hydrogenation isomerization reaction of long-chain normal alkanes.
[0027] A fourth aspect of the present invention provides a method for reducing acid sites and altering the distribution of acid sites in ZSM-48 molecular sieves by shortening the hydrothermal synthesis time. By shortening the reaction time during the hydrothermal synthesis of the molecular sieve and forcibly halting the growth of the molecular sieve crystals through water cooling, the present invention reduces the relative crystallinity of the molecular sieve, thereby enhancing the isomerization performance of the catalyst supported by the molecular sieve.
[0028] The fifth aspect of the present invention provides an application of the low relative crystallinity ZSM-48 molecular sieve described in the first aspect of the present invention for the hydroisomerization reaction of long-chain normal alkanes. The low relative crystallinity ZSM-48 molecular sieve described in claim 1 is used as a carrier, and is loaded with precious metal platinum and used for the hydroisomerization reaction of long-chain normal alkanes, which can improve the selectivity of isoalkanes and increase the proportion of single-branched products.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention shortens the hydrothermal synthesis reaction time of ZSM-48 molecular sieve during the hydrothermal synthesis stage, forcibly interrupts the growth of molecular sieve crystals by water cooling, thereby reducing the relative crystallinity of the molecular sieve and preparing a ZSM-48 molecular sieve with low relative crystallinity. Molecular sieves are usually synthesized by a hydrothermal method. First, a mixed silicon precursor and an aluminum precursor form a primary amorphous phase mixture; during the heating process, the components in the solid phase and the liquid phase are redistributed to approach equilibrium, at which time the solid phase is called a secondary amorphous phase mixture; then, a partially regular structure, i.e., a crystal nucleus, is formed on certain "ordered islands" containing a template; the crystalline units decomposed from the amorphous part grow in connection on the crystal nucleus until the amorphous matrix is consumed and the crystals reach equilibrium with the mother liquid components. In the present invention, the growth of the molecular sieve is terminated by water cooling, the relative crystallinity of the molecular sieve crystals is adjusted, the acid sites of the molecular sieve crystals are reduced, and the distribution of the acid sites is changed.
[0031] 2. The present invention regulates the relative crystallinity of ZSM-48 molecular sieve crystals by controlling the reaction time of the molecular sieve hydrothermal synthesis stage. Specifically, ZSM-48 molecular sieve crystals with a suitable relative crystallinity are prepared during the hydrothermal synthesis for 38-56 hours.
[0032] 3. In the preparation method of the present invention, the growth of molecular sieve crystals needs to be forcibly terminated by water cooling.
[0033] 4. Experiments have shown that at the respective optimal isomerization reaction temperatures, that is, at the reaction temperatures at which each catalyst reaches the highest isomerization rate, the isomerization rate and isomerization selectivity of the catalyst with shortened hydrothermal synthesis time are greatly improved compared to ordinary catalysts with normal synthesis time. The molar ratio of multi-branched products to single-branched products in the comparative example is 0.6758, while that in Example 1 drops to 0.3737. The above results show that the ZSM-48 molecular sieve catalyst with low relative crystallinity obtained by the present invention is applied to the hydroisomerization reaction of normal alkanes. Due to its fewer acid sites and suitable acid site distribution, it is possible to obtain an isomerized alkane mixture with high selectivity, inhibit the formation of cracking products, and significantly increase the proportion of single-branched products. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1SEM images of Sample 1 and Sample 6 in Example 1 and Example 6; (a) Sample 6, (b) Sample 1;
[0035] Figure 2 TEM image of sample 1 in Example 1;
[0036] Figure 3 XRD (X-ray diffractometer) analysis of samples 1-6 in Examples 1-6;
[0037] Figure 4 is the SEM image of sample 2 in Example 2;
[0038] Figure 5 is the SEM image of sample 3 in Example 3;
[0039] Figure 6 is the SEM image of sample 4 in Example 4;
[0040] Figure 7 is the SEM image of sample 5 in Example 5;
[0041] Figure 8 The catalyst obtained by using the molecular sieve of sample 6 as a carrier and loading precious metal platinum in Example 6 was used in the hydrogenation isomerization reaction of n-hexadecane. The isomerization rate, isomerization selectivity, and the ratio of single-branched isomerized products to multi-branched isomerized products in the isomerized products were evaluated.
[0042] Figure 9 The catalyst obtained by using the molecular sieve of sample 1 as a carrier and loading precious metal platinum in Example 1 was used in the hydrogenation isomerization reaction of n-hexadecane, and the isomerization rate, isomerization selectivity, and the ratio of single-branched isomerized products to multi-branched isomerized products in the isomerized products were evaluated. DETAILED DESCRIPTION
[0043] The present invention will be described in further detail below with reference to the accompanying drawings and specific embodiments. It should be noted that the following examples are illustrative and not restrictive, and the scope of the present invention cannot be limited by the following examples. The raw materials required in the following examples and comparative examples are all commercially available.
[0044] Example 1: (Hydrothermal synthesis 44h)
[0045] Completely dissolve 2.36g of NaOH in 41.63g of deionized water. Slowly add 5.0g of white carbon black to the solution and stir for 30 minutes. Then, add 3.01g of hexamethylammonium bromide and stir for 30 minutes. Finally, dropwise add 20.90g of an aqueous aluminum sulfate solution (prepared from 0.30g of Al2(SO4)3·18H2O, 18.82g of deionized water, and 1.78g of concentrated sulfuric acid) and stir for 30 minutes. Seal the polytetrafluoroethylene liner in a stainless steel high-pressure hydrothermal autoclave, secure the autoclave in a homogeneous reactor, and crystallize at autogenous pressure of 160°C for 44 hours.
[0046] The crystallized product was removed, cooled, filtered, and washed until the filtrate was neutral. It was then dried in a 120°C oven. The product was then placed in a muffle furnace and heated at a rate of 1°C / min to 540°C, held for 3 hours, then heated at a rate of 1°C / min to 595°C, held for 3 hours, and then cooled to room temperature at a rate of 1°C / min. The resulting powder was sodium ZSM-48. The powder was then dispersed in a 1 mol / L aqueous ammonium chloride solution with a liquid-to-solid ratio of 10, refluxed at 80°C for 4 hours, filtered, and dried in a 120°C oven. The ion exchange process was repeated twice. Finally, the sample was calcined in a muffle furnace: heated at a rate of 5°C / min to 550°C, held for 4 hours, and then cooled to room temperature at a rate of 1°C / min. The resulting powder was the hydrogen-type molecular sieve. This yielded ZSM-48 molecular sieve sample 1 with low relative crystallinity.
[0047] The obtained product was analyzed by XRD (X-ray diffractometer) to determine that its structure was ZSM-48 molecular sieve, and the peak intensity was weaker than that of the comparative example. Figure 3 . SEM images such as Figure 1 As shown in b, the aggregate size and crystal length are smaller than those of the comparative example. Figure 2 TEM image of sample 1 in Example 1. Figure 1 As can be seen from b, the ZSM-48 molecular sieve has aggregates of 1 to 3 μm, and the aggregates are composed of crystal clusters growing in multiple directions. Figure 2 It can be seen that the crystals in the cluster are columnar, with a diameter of 10 to 40 nm, a length of 100 to 400 nm, and a width of about 25 nm for a single crystal.
[0048] Example 2: (Hydrothermal synthesis 38h)
[0049] The specific implementation conditions are similar to those in Example 1, but the crystallization time is 38h. The obtained molecular sieve is determined to be ZSM-48 molecular sieve by XRD analysis. The peak intensity is weaker than that in Example 1. Figure 3 The SEM image analysis shows that the aggregate size and crystal length are smaller than those in Example 1, and there is a more obvious amorphous phase. Figure 4 .
[0050] Example 3: (Hydrothermal synthesis 40h)
[0051] The specific implementation conditions are similar to those of Example 1, but the crystallization time is 40 hours. The molecular sieve obtained is determined to be ZSM-48 molecular sieve by XRD analysis, and the peak intensity is slightly stronger than that of Example 2. Figure 3 The SEM image analysis shows that the aggregate size and crystal length are smaller than those in Example 1. At this time, the amorphous phase is basically not observed. Figure 5 .
[0052] Example 4: (Hydrothermal synthesis 42h)
[0053] The specific implementation conditions are similar to those of Example 1, but the crystallization time is 42 hours. The molecular sieve obtained is determined to be ZSM-48 molecular sieve by XRD analysis, and the peak intensity is slightly stronger than that of Example 3. Figure 3 The SEM image analysis shows that the aggregate size and crystal length are smaller than those in Example 1. Figure 6 .
[0054] Example 5: (Hydrothermal synthesis 46h)
[0055] The specific implementation conditions are similar to those of Example 1, but the crystallization time is 46 hours. The obtained molecular sieve is determined to be ZSM-48 molecular sieve by XRD analysis. The peak intensity is slightly stronger than that of Example 1, but lower than that of the comparative example. The SEM image analysis shows that the aggregate size and crystal length are larger than those of Example 1. Figure 7 .
[0056] Example 6: (Hydrothermal synthesis 48h), this example is used as a comparative example
[0057] The specific implementation conditions are similar to those of Example 1, but the crystallization time is 48 hours. The obtained molecular sieve is determined to be ZSM-48 molecular sieve by XRD analysis, and the peak intensity is the strongest among all the examples. The SEM image analysis shows that the aggregate size and crystal length are the largest among all the examples, as shown in FIG. Figure 1 a.
[0058] Example 7: Hydroisomerization reaction of n-hexadecane
[0059] The molecular sieve sample 1 with a relatively low relative crystallinity obtained in Example 1 and the ordinary ZSM-48 molecular sieve sample 6 obtained in the comparative example were used as carriers, loaded with precious metal platinum, and applied to the hydrogenation isomerization reaction of n-hexadecane. The loading amount of platinum was 0.5wt%. The loading method was as follows: 5g of chloroplatinic acid in ethanol (0.02mol / L) was added to 5g of ZSM-48 molecular sieve in ethanol (0.1g / mL), refluxed at 75°C for 1h, and evaporated to dryness using a rotary evaporator. Afterwards, the mixture was calcined in a muffle furnace, heated to 450°C at a heating rate of 1°C / min, maintained for 4h, then cooled to room temperature at a cooling rate of 1°C / min, and formed into particles of 20 to 40 mesh sizes using a tablet press. The catalyst was loaded into a micro-fixed bed reactor and filled with silicon carbide at both ends. Before the evaluation began, the mixture was reduced at 400°C for 4h under a hydrogen atmosphere. The reaction conditions were: pressure 3MPa, air velocity 2h -1 , hydrogen-oil ratio 1000, temperature 260~300℃.
[0060] The isomerization rate, isomerization selectivity, and ratio of single-branched isomerization product to multi-branched isomerization product in the isomerization products of the two catalysts of Sample 6 of Example 6 and Sample 1 of Example 1 are shown as follows: Figure 8 、 Figure 9 shown.
[0061] The product analysis results at the respective optimal isomerization reaction temperatures are shown in Table 1.
[0062] As can be seen from Table 1, at the respective optimal isomerization reaction temperatures, that is, at the reaction temperatures at which each catalyst reaches the highest isomerization rate, the isomerization rate and isomerization selectivity of the catalyst with low relative crystallinity are greatly improved compared to the normal crystallization ordinary catalyst. The molar ratio of multi-branched products to single-branched products in the comparative example is 0.6758, while that in Example 1 drops to 0.3737. The above results illustrate that the ZSM-48 molecular sieve catalyst with low relative crystallinity obtained by the present invention is applied to the isomerization and degassing reaction of normal alkanes. Due to its fewer acidic sites, it is possible to obtain an isomerized alkane mixture with high selectivity, inhibit the formation of cracking products, and significantly increase the proportion of single-branched products.
[0063] Table 1 Comparison of catalytic performance results
[0064]
[0065]
Note
[0066] The above is an exemplary description of the present invention. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by other skilled in the art without expending creative labor falls within the scope of protection of the present invention.
Claims
1. A ZSM-48 molecular sieve with low relative crystallinity, characterized in that: The ZSM-48 molecular sieve has a relatively low crystallinity. The ZSM-48 molecular sieve has aggregates of 1 to 3 μm, and the aggregates are composed of crystal clusters growing in multiple directions. The crystals in the crystal clusters are columnar, with a diameter of 10 to 40 nm and a length of 100 to 400 nm.
2. A method for preparing the low relative crystallinity ZSM-48 molecular sieve according to claim 1, characterized in that: It includes the following steps: (1) adding deionized water, alkali solution, template solution, silicon source, and aluminum source into a crystallization kettle, stirring and mixing, and then subjecting the mixture to a crystallization reaction. After a certain reaction time, quenching the hydrothermal reaction by water cooling; (2) washing the product after the crystallization reaction until it is neutral, centrifuging or filtering, and drying to obtain an incompletely crystallized ZSM-48 molecular sieve; (3) calcining the incompletely crystallized ZSM-48 molecular sieve in a muffle furnace to remove the template agent to obtain a Na / K-ZSM-48 molecular sieve; (4) The Na / K-ZSM-48 molecular sieve is converted into a hydrogen-type ZSM-48 molecular sieve to obtain a H-ZSM-48 molecular sieve with low relative crystallinity.
3. The preparation method according to claim 2, characterized in that: In step (1), the aluminum source is selected from silica-alumina sol, sodium aluminate or aluminum sol; the silicon source is selected from silica sol, silica aerosol, tetraethyl orthosilicate or sodium silicate with a SiO2 content of 30% to 40%; the alkali solution is an aqueous solution of NaOH or KOH with a molar concentration of 0.5 to 1.5 mol / L; and the template agent is selected from one or more of hexamethylammonium bromide, pentamethylammonium bromide and 1,6-hexanediamine.
4. The preparation method according to claim 3, characterized in that: The molar ratio of the aluminum source, water, alkali solution, template solution and silicon source in step (1) is: The amount of alkali solution is OH - The aluminum source is calculated as Al2O3, the silicon source is calculated as SiO2, wherein Q represents a template.
5. The preparation method according to claim 2, characterized in that: In step (1), the crystallization reaction temperature is 100-260° C., and the crystallization reaction time is 38-48 hours; in step (2), the drying temperature is 100-200° C., and the drying time is 2-6 hours.
6. The preparation method according to claim 2, characterized in that: The calcination conditions in step (3) are: first calcining at 500-600°C for 5-8h, and then calcining at 600-700°C for 4-6h.
7. The preparation method according to claim 2, characterized in that: The method for converting the Na / K-ZSM-48 molecular sieve into the H-ZSM-48 molecular sieve in step (4) is to disperse the Na / K-ZSM-48 molecular sieve in a 0.5-1.5 mol / L aqueous solution of ammonium chloride, reflux at 70-90° C. for 2-6 hours, and dry at 100-150° C. to perform ion exchange, and then calcine in a muffle furnace at 500-600° C. for 2-6 hours to obtain the H-ZSM-48 molecular sieve; the ion exchange step can be performed multiple times to ensure complete ion exchange.
8. A ZSM-48 molecular sieve catalyst loaded with precious metal platinum, characterized in that: The ZSM-48 molecular sieve with low relative crystallinity as claimed in claim 1 is used as a carrier.
9. A method for improving the isomerization performance of ZSM-48 molecular sieve by reducing the relative crystallinity of the molecular sieve, characterized in that: In the ZSM-48 molecular sieve synthesis stage, the hydrothermal synthesis time is shortened.
10. An application of the monodisperse ZSM-48 molecular sieve according to claim 1 for the hydroisomerization reaction of long-chain normal alkanes, characterized in that: The low relative crystallinity ZSM-48 molecular sieve described in claim 1 is used as a carrier to load precious metal platinum and then used for the hydrogenation isomerization reaction of long-chain normal alkanes, which can improve the selectivity of isoalkanes and increase the proportion of single-branched products.